Inspiration from the decorations of the holy mosque of the Prophet in the creation of modern metal jewelry - Alrehaili, Sarah Saleem; Qurban, Massoudah Alem (Journal of Humanities & Social Sciences, 2020)
The aim of this study is to create modern metal jewelry inspired from the formal and aesthetic characteristics of the decoration of the Prophet’s Mosque, Where the study seeks to introduce the history of the Prophet’s Mosque and the stages of development of Islamic decorations, in addition to addressing their types and aesthetic values. It also includes the discovery of minerals, types and techniques of their formation, and the study of some metal jewelry inspired by Islamic decoration throughout history, and reached a number of results, the most important; The possibility of creating contemporary Islamic jewelry that mimics the designs of modern times. It also reached a number of recommendations, including trying to synthesize more than one technique in the formation of metal jewelery, which gives an aesthetic appeal to the piece. Where the researcher follows the descriptive analytical approach to a sample of the decorations of the Prophet’s Mosque, and the applied approach to the implementation of the research experience.